2003
DOI: 10.1105/tpc.013839
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Basic/Helix-Loop-Helix Transcription Factor Family[W]

Abstract: The basic/helix-loop-helix (bHLH) proteins are a superfamily of transcription factors that bind as dimers to specific DNA target sites and that have been well characterized in nonplant eukaryotes as important regulatory components in diverse biological processes. Based on evidence that the bHLH protein PIF3 is a direct phytochrome reaction partner in the photoreceptor's signaling network, we have undertaken a comprehensive computational analysis of the Arabidopsis genome sequence databases to define the scope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

57
1,227
1
8

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,136 publications
(1,330 citation statements)
references
References 74 publications
57
1,227
1
8
Order By: Relevance
“…In plants, miRNA genes are mostly discrete, independent transcription units, and about 50% of miRNAs are predicted to be multiple loci in the genome, similar to that seen with protein-coding genes (recent rice sequencing data showed that 29% of protein-coding genes appear in gene families) [43]. The evidence here suggesting that the expansion of miRNA genes in plants resulted from genome segmental and tandem duplication events during evolution is similar to that of many protein-coding gene families, especially transcription factor families [33,44]. Thus, these kinds of duplication events are proposed to have contributed to the expansion of both protein-coding gene families and miRNA gene families.…”
Section: Discussionsupporting
confidence: 65%
“…In plants, miRNA genes are mostly discrete, independent transcription units, and about 50% of miRNAs are predicted to be multiple loci in the genome, similar to that seen with protein-coding genes (recent rice sequencing data showed that 29% of protein-coding genes appear in gene families) [43]. The evidence here suggesting that the expansion of miRNA genes in plants resulted from genome segmental and tandem duplication events during evolution is similar to that of many protein-coding gene families, especially transcription factor families [33,44]. Thus, these kinds of duplication events are proposed to have contributed to the expansion of both protein-coding gene families and miRNA gene families.…”
Section: Discussionsupporting
confidence: 65%
“…bHLHs form one of the largest families of TFs in plants and regulate numerous processes. Analysis of the bHLH family is technically more difficult than for most of the other TF families Heim et al, 2003;Toledo-Ortiz et al, 2003); therefore, we performed a total of 30 independent searches using a representative bHLH domain from each of the 23 subfamilies described by Heim et al (2003). This resulted in the identification of 192 bHLH sequences representing a minimum of 190 bHLH genes.…”
Section: The Bhlh Familymentioning
confidence: 99%
“…Atchley et al (1999) computed and deduced a predictive motif for the bHLH domains based on 242 bHLH proteins, in which 19 conserved sites were found within the bHLH domain (Atchley et al, 1999). Their works showed that a sequence identified with less than 8 mismatches to the predictive motif was possibly a bHLH protein (Atchley and Fitch, 1997;Atchley et al, 1999;Atchley et al, 2000) and other researchers found that a sequence with nine mismatches might be a potential bHLH protein as well (Toledo-Ortiz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more and more bHLH genes has been identified and bHLH TF families have been analyzed in many organisms whose genome drafts have been available (Ledent et al, 2002;Toledo-Ortiz et al, 2003;Buck and Atchley, 2003;Heim et al, 2003;Li et al, 2006a, b;Simionato et al, 2007;Stevens et al, 2008;Wang et al, 2007Wang et al, , 2008Wang et al, , 2009Pires and Dolan, 2010;Carretero-Paulet et al, 2010;Liu andZhao, 2010, 2011;Liu et al, 2012Liu and Chen, 2013). However, the family of bHLH TFs has not yet been studied and characterized in Xenopus laevis.…”
Section: Introductionmentioning
confidence: 99%